Individual learning paths mastering teachers’ professional vision - Oellers, Manuel; Junker, Robin; Holodynski, Manfred (Frontiers in Education, 2024)
Promoting a professional vision of teaching as a key factor of teachers’ expertise is a core challenge for teacher professionalization. While the research on teaching has evolved and successfully evaluated various intervention programs, a prevailing emphasis on outcome measures can be observed. However, the learning processes by which teachers acquire professional vision currently remain a black box. The current study sought to fill this research gap. As part of a course dedicated to promoting a professional vision of classroom management, students were imparted knowledge about classroom management that had to be applied to the analysis of authentic classroom videos. The aims of the study were to determine the variety of individual strategies that students applied during their video analyses, and to investigate the relationship between these and the quality of the students’ analyses, measured by their agreement with an experts’ rating of the video clips. The sample comprised 45 undergraduate pre-service teachers enrolled in a course to acquire a professional vision of classroom management. By applying their imparted knowledge of classroom management, students engaged in the analysis of classroom videos to learn how to notice and interpret classroom events that are relevant for effective classroom management. Implementing a learning analytical approach allowed for the gathering of process-related data to analyze the behavioral patterns of students within a digital learning environment. Video-based strategies were identified by conducting cluster analyses, and related to the quality of the students’ analysis outcomes, measured by their concordance with the experts’ ratings. We gained insight into the learning processes involved in video-based assignments designed to foster a professional vision of classroom management, such as the areas of interest that attracted students’ heightened attention. We could also distinguish different approaches taken by students in analyzing classroom videos. Relatedly, we found clusters indicating meticulous and less meticulous approaches to analyzing classroom videos and could identify significant correlations between process and outcome variables. The findings of this study have implications for the design and implementation of video-based assignments for promoting professional vision, and may serve as a starting point for implementing process-based diagnostics and providing adaptive learning support.